If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x-13+4x=-10+9x+15
We move all terms to the left:
2x-13+4x-(-10+9x+15)=0
We add all the numbers together, and all the variables
2x+4x-(9x+5)-13=0
We add all the numbers together, and all the variables
6x-(9x+5)-13=0
We get rid of parentheses
6x-9x-5-13=0
We add all the numbers together, and all the variables
-3x-18=0
We move all terms containing x to the left, all other terms to the right
-3x=18
x=18/-3
x=-6
| 1/3(2b+9/2)=2/3(b=9/2) | | 4r-5=13+16 | | X-5=7+x- | | 1÷2h+1÷3(h-6)=5÷6h+2 | | —27+20w=73 | | (5x-3)^2+9=0 | | 2/5x+1=-11 | | 12-a+5a=4 | | 4(b+24)=8b+12 | | 9x-6x=-18 | | -2/3x+5=20 | | 2y+y=-21 | | -4x-4x=12 | | 6n-9=59 | | 4f+8=-10+3f | | -5(-5x+5)=-4 | | 5*(3y-1)-3*(2y)=10 | | 2z^2=10 | | X+0,5x+0,2x=51 | | 14/15=n/6 | | 3n+-2=-15 | | 4x+20+5x+25=180 | | -48=15+7x | | 3(-2x+7)=-6 | | -u+201=131 | | 2/3y=22/5 | | 3a+12=6a | | 180-w=114 | | 11y-253=9y-187 | | 3x+3=8x+6 | | 4-48b=6-48b+3 | | 2(3t-5)+5=3t+7 |